Dampak Inflasi, Kurs Rupiah Dan Suku Bunga Terhadap Return Saham (Studi Pada Perusahaan LQ45 Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2021) - Novira Pusdayana; Cut Delsie Hasrina; Marah Sutan Rangkuti; Rizki Akbar (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Abstract: When investing funds in a company, an investor must pay attention to the stock returns they will receive. Apart from that, investors must also pay attention to the company's performance as well as other factors such as: inflation, Rupiah exchange rate and interest rates and so that investors can benefit from the investment. This study aims to find out the impact of inflation, Rupiah exchange rate and interest rates on stock returns in LQ45 companies listed on the Indonesia Stock Exchange for the 2016-2021 period. to determine the impact of the rupiah exchange rate on stock returns in LQ45 companies listed on the Indonesia Stock Exchange for the 2016-2021 period. To find out the impact of interest rates on stock returns in LQ45 companies listed on the Indonesia Stock Exchange for the 2016-2021 period. To determine the impact of inflation, interest rates, and the rupiah exchange rate on stock returns in LQ45 companies listed on the Indonesia Stock Exchange for the 2016-2021 period. research used is quantitative research. This study uses purposive sampling, data collection techniques namely documentation. The data analysis technique in this study is to use multiple linear regression results. The results of the t-test statistical analysis for the inflation variable have a significant negative effect on stock returns in LQ45 companies listed on the Indonesia Stock Exchange for the 2016-2021 period. The results of the t-test statistical analysis for the rupiah exchange rate variable have a negative and significant effect on stock returns in LQ45 companies listed on the Stock Exchange Indonesia for the 2016-2021 period. The results of the t-test statistical analysis for the interest rate variable have a negative and significant effect on stock returns at LQ 45 companies listed on the Indonesia Stock Exchange for the 2016-2021 period. Inflation, interest rates and rupiah exchange rates simultaneously and significantly affect stock returns.